2010
DOI: 10.2478/v10065-010-0057-1
|View full text |Cite
|
Sign up to set email alerts
|

Associative memory in artificial immune systems

Abstract: The paper concentrates on analyzing associative properties of Artificial Immune Systems, especially on immunological memory, which is a member of a class of sparse and distributed associative memories [18]. This class of memories derives its associative and robust nature by sparsely sampling the input space and distributing the data among many independent agents [16]. Immunological memory is one of the defining characteristics of the adaptive immune system [4]. This memory is able to store and recall patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Moreover, KPFM under illumination is a well-established method to measure surface photovoltage (SPV) and charge carrier lifetime over organic and inorganic materials [21][22] [23]. In addition, previous study reports that charge carrier lifetime measured by KPFM through SPV can be sensitive to defects even when embedded in silicon dioxide [24]. However, until now the use of KPFM under illumination to study passivation of buried interface has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, KPFM under illumination is a well-established method to measure surface photovoltage (SPV) and charge carrier lifetime over organic and inorganic materials [21][22] [23]. In addition, previous study reports that charge carrier lifetime measured by KPFM through SPV can be sensitive to defects even when embedded in silicon dioxide [24]. However, until now the use of KPFM under illumination to study passivation of buried interface has not been reported.…”
Section: Introductionmentioning
confidence: 99%